Inhibitory activity of fermentation filtrate of red passion fruit pulp (Passiflora edulis sims.) against Escherichia coli extended-spectrum beta-lactamase (ESBL) and methicillin resistant Staphylococcus aureus (MRSA) - Iif Hanifa Nurrosyidah; Ni Made Mertaniasih; Isnaeni (The East Java Biological Society, 2020)
This study aims to determine the minimum inhibitory concentration (MIC) and bactericidal concentration (MBC) of the fermentation filtrate (FF) on red passion fruit pulp (Passiflora edulis Sims.) against Escherichia coli Extended Spectrum Beta Lactamase (ESBL) and Methicillin Resistant Staphylococcus aureus (MRSA). The method used was the fermentation of red passion fruit pulp for 24 h using De Man Rogosa Sharpe Broth (MRS-broth) media, and the result showed that the FF of red passion fruit pulp made a dilution series concentration of 50%, 25%, 12.5%, 6.25%. Considering this result, the MIC FF of red passion fruit cells against ESBL and MRSA has a 25% dilution concentration, while MBC has a 50% dilution concentration. This shows that red passion fruit has the potential to be developed as antibacterial material, especially to fight bacteria that are already resistant.